An Analysis of West Country Dialect Used by Hagrid in J.K. Rowling's Harry Potter (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
English, like other languages, owns distinctive varieties that enrich the language itself. Dialect is one of the interesting topics which grabs linguists' attention to analyze. This paper analyzes one of the English dialect, called West Country, in a novel entitled Harry Potter and The Sorcerer's Stone by J.K. Rowling. Hagrid, a gatekeeper of Hogwarts School uses unique utterances that differ from other characters' utterances in the novel. The writer employed descriptive research since the analysis is about discussing, analyzing, and finding the dialect patterns. The data of this study are taken from one of the novels in Harry Potter and The Sorcerer's Stone. The three important features which were found in the dialect varied in terms of the phonology features, the grammatical pattern, and the vocabulary variation. This study shows that Rowling attributes the dialect to Hagrid for a reason that people from West Country are very simple and humble.